Binding of Thiostrepton to Ribosomes from Thiostrepton-Sensitive and -Resistant Bacillus subtilis Strains - Vince, Robert (1976)
Binding of [(35)S]thiostrepton to ribosomes from thiostrepton-sensitive and -resistant strains of Bacillus subtilis was studied. Ribosomes from thiostrepton-resistant strains bound relatively little thiostrepton compared with ribosomes from thiostrepton-sensitive B. subtilis. In addition, ribosomes from revertant strains that were obtained as thiostrepton-sensitive revertants from thiostrepton-resistant strains bound [(35)S]thiostrepton similarly to ribosomes from the sensitive parental strain.